2012
DOI: 10.1002/pen.23201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clay on the corrosion inhibition and dynamic mechanical properties of epoxy ester–polyurea–polysiloxane hybrid coatings

Abstract: The corrosion resistance of polymeric coatings containing epoxy ester, polyurea, and polymethylhydrosiloxane was significantly improved by the addition of cloisite 15A organoclay. The weight percent of organoclay was varied from 0.5 to 10%. The presence of organoclay in the coatings was confirmed using the Fourier transformed infrared spectroscopy. The effect of organoclay on the surface energy of the coatings was analyzed by measuring contact angle with a video contact angle analyzer and using water and iodom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Hence, significance of enhancing the mechanical and environmental properties of polyurethane is out of question. Recently, using nanoparticles such as silica, TiO 2 , and clay became a new way for reinforcement and improving the coating properties . Sabzi showed that the presence of modified nano TiO 2 particles in the polyurethane coating can improve the mechanical properties significantly .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, significance of enhancing the mechanical and environmental properties of polyurethane is out of question. Recently, using nanoparticles such as silica, TiO 2 , and clay became a new way for reinforcement and improving the coating properties . Sabzi showed that the presence of modified nano TiO 2 particles in the polyurethane coating can improve the mechanical properties significantly .…”
Section: Introductionmentioning
confidence: 99%
“…Although only a small proportion of rGO was incorporated into the silicone-acrylate resin film, high corrosion protection was afforded. By comparison with that of siliconeacrylate resin film in the previous works [11,24,25], the corresponding corr of rGO/silicone-acrylate resin composite film was smaller. The good corrosion resistance may be attributed to the following two reasons: (1) silicone-acrylate resin could act as a physical barrier coating and (2) the welldispersed rGO embedded in silicone-acrylate resin matrix could prevent corrosion owing to a relatively higher aspect ratio than clay platelets, which enhances the oxygen barrier property of rGO/silicone-acrylate resin composite film [10,25].…”
Section: Mechanical Properties and Erosion Resistance Of Rgo/ Siliconmentioning
confidence: 59%